Implementasi Inovasi Pembelajaran “Gadis Ceria” pada Mata Pelajaran Pendidikan Pancasila - Sutrisno Sutrisno; Erna Yayuk; Lud Waluyo (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2026)
This study aims to describe the implementation, supporting and inhibiting factors, and solutions to the obstacles of the "Gadis Ceria" learning innovation. This study used a qualitative descriptive approach. Data were collected through observation, in-depth interviews, and documentation. Data analysis used an interactive model that includes data reduction, data presentation, and conclusion drawing, while data validity was tested through source and technique triangulation. The results of the study indicate that the implementation of "Gadis Ceria" is able to create an interactive, creative, and student-centered learning atmosphere. Supporting factors for the implementation of the "Gadis Ceria" learning innovation include school support, teacher competence, student creativity, and the availability of facilities and infrastructure, while inhibiting factors include limited time, internet connection, variations in students' technological abilities, and resistance to change. The constraint of limited time can be overcome through redesigning learning allocations, integrating activities, and implementing blended learning; addressing variations in students' technological abilities through scaffolding strategies; and minimizing resistance to change through training, ongoing mentoring, and strengthening communication.